A resilience systemic model for assessing critical supply chain disruptions. Issue 5 (1st July 2022) - Oliver, Everett; Mazzuchi, Thomas; Sarkani, Shahram
Abstract: Assessing the impact of natural disasters and manmade incidents against critical infrastructure systems is important and challenging. As critical infrastructure sectors become more interdependent, a method is needed to assess how disruptions to one sector affect other sectors. This need is particularly significant in the case of critical national supply chains which have not received the same attention as other critical infrastructure systems. This research develops a methodology for performing supply chain impact assessments by integrating model‐based systems engineering (MBSE) with discrete event simulation (DES). SysML models capture the supply chain structure and critical infrastructure interdependencies. Simulation of the supply chain model subjected to external constraints identifies the impacts from critical infrastructure disruptions. This approach enables researchers and public policy planners to assess critical supply chain risks associated with current infrastructure implementations, and to conduct what‐if analyses on alternative solutions. Application of this methodology to assess the natural disaster impacts on an urban food supply system demonstrates the effectiveness of modeling and simulation for evaluating the impacts of critical infrastructure disruptions on a wide range of critical supply chains. Future research should apply this methodology to different national supply chains and investigate additional critical infrastructure interdependency linkage mechanisms.